Pengaruh fun workplace dan work environment terhadap work engagement melalui job sastisfaction pada tenaga kependidikan di perguruan tinggi - Grace Olivia Wakum; Budiono (Jurnal Ilmu Manajemen, 2026)
This research aims to determine and explain the effect of fun workplace and work environment on work engagement through job satisfaction on educational staff at a public university. This research is classified as quantitative research with a population of 50 university educational staff, and the sampling technique used is a saturated sampling method, resulting in a total sample of 50 respondents. The statistical analysis used in this research was Structural Equation Modeling (SEM) with the help of SmartPLS software. The results of this research show that fun workplace has no significant effect on work engagement, work environment has a significant positive effect on work engagement, job satisfaction has a significant positive effect on work engagement, fun workplace has a significant positive effect on job satisfaction, work environment has a significant positive effect on job satisfaction, job satisfaction is able to mediate the effect of a fun workplace on work engagement, and job satisfaction is able to mediate the effect of the work environment on work engagement. The implications of this study suggest that to enhance the effectiveness of the fun workplace program, institutions should incorporate fun into daily routines instead of depending only on occasional major events. This includes morning briefings with ice breakers and informal interaction spaces. These should be aligned with the faculty’s formal culture to ensure appropriateness. Furthermore, the study suggests supportive leadership approach including constructive feedback, task rotation, and fair performance evaluations to improve staff well-being and development.